Bangunan Pentadbiran Kerajaan British, Jalan Taming Sari, 34000 Taiping, Perak Darul Ridzuan - Asmawi Azmar Othman; Norhafiszah Abdullah; Normafizah Markaban; Raja Sahily Raja Jaafar; Rosmasabrina Roslan; Saiful Azri Mohd Husain; Saiful Fazli Ramli; Shahrul Nazman Mohd Najib (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Measured Drawing (Jabatan Senibina)) - Universiti Teknologi Malaysia, 2000